Editorial: Beyond urban violence - Tulumello, Simone (2021)
Not many topics have received the amount of (academic, cultural, political) attention that urban violence has had. In a way, since 19th century reflections on the nascent urban modernity, the discourse about ‘the city’ has always been one of violence, with remarkable consequences in the way cities are discussed, regulated, planned, policed, and lived. Reflection on what urban violence may actually be, however, has been for the most part lacking. The urban in urban violence has often been used as a mere adjective pointing at the location where a physical event of violence takes place, rather than a process, a space, an atmosphere, which may be violent in the first place. In this sense, going beyond a narrow understanding of urban violence means attending to its relational, material, and temporal complexity. This is what the following contributions do.